2018
DOI: 10.1186/s12879-018-3641-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an outbreak of enterovirus-associated meningitis in Mossel Bay, South Africa, December 2015–January 2016

Abstract: BackgroundHuman enteroviruses (HEVs) are common causal agents of aseptic meningitis in young children. Laboratory and syndromic surveillance during December 2015 and January 2016 noted an unusually high number of paediatric aseptic meningitis cases at a hospital in Mossel Bay, Western Cape Province, South Africa. HEV was detected in clinical samples, prompting an outbreak investigation.MethodsEpidemiological investigations were conducted to ascertain possible linkage between cases. Amplification, sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Type E30 showed an extraordinary peak in the proportion of genotypes, mainly in Europe, and was the most frequent EV detected in patients with neurological symptoms. This is in line with frequent reports of outbreaks of E30 related meningitis, both in Europe and in other continents [ 59 , 60 , 61 , 62 ], and with seroepidemiological studies reporting high rates of E30 seropositivity already in young age groups [ 63 ]. E30 has been reported to be genetically diverse, containing multiple lineages that co-circulate within populations [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…Type E30 showed an extraordinary peak in the proportion of genotypes, mainly in Europe, and was the most frequent EV detected in patients with neurological symptoms. This is in line with frequent reports of outbreaks of E30 related meningitis, both in Europe and in other continents [ 59 , 60 , 61 , 62 ], and with seroepidemiological studies reporting high rates of E30 seropositivity already in young age groups [ 63 ]. E30 has been reported to be genetically diverse, containing multiple lineages that co-circulate within populations [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that EV infection has typical seasonal feature in temperate climates. This is consistent with other studies showing that most aseptic meningitis occur in summer and autumn, and less frequent in the spring and winter [11,32].…”
Section: Discussionsupporting
confidence: 93%
“…Nonpolio human enteroviruses (EVs), especially the species enterovirus B (EV-B), are the most common etiology for this disease [6]. Various studies over the past several decades have shown that most EV-B types are the major causative agents for this disease, and numerous EV-Bs associated meningitis outbreaks have been reported throughout the world [7,8,9,10,11,12,13]. Shandong is a coastal province in China.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed that 45% (135/301) of the EV-positive cases occurred from September to November (spring season), although cases also occurred in other seasons. Conversely, other studies reported that aseptic meningitis cases in the southern hemisphere countries occurred more frequently during the summer season, such as Australia [25] and South Africa [26]. The discrepancy in this seasonal distribution could be due to whether the source of specimen is from a sporadic case or from an outbreak.…”
Section: Discussionmentioning
confidence: 95%